Pneumococci in biofilms are non-invasive: implications on nasopharyngeal colonization - Gilley, Ryan P.; Orihuela, Carlos J. (Frontiers in Cellular and Infection Microbiology, 2014)
Streptococcus pneumoniae (the pneumococcus) is an opportunistic pathogen that colonizes the human nasopharynx asymptomatically. Invasive pneumococcal disease develops following bacterial aspiration into the lungs. Pneumococci within the nasopharynx exist as biofilms, a growth phenotype characterized by surface attachment, encasement within an extracellular matrix, and antimicrobial resistance. Experimental evidence indicates that biofilm pneumococci are attenuated vs. their planktonic counterpart. Biofilm pneumococci failed to cause invasive disease in experimentally challenged mice and in vitro were shown to be non-invasive despite being hyper-adhesive. This attenuated phenotype corresponds with observations that biofilm pneumococci elicit significantly less cytokine and chemokine production from host cells than their planktonic counterparts. Microarray and proteomic studies show that pneumococci within biofilms have decreased metabolism, less capsular polysaccharide, and reduced production of the pore-forming toxin pneumolysin. Biofilm pneumococci are predominately in the transparent phenotype, which has elevated cell wall phosphorylcholine, an adhesin subject to C-reactive protein mediated opsonization. Herein, we review these changes in virulence, interpret their impact on colonization and transmission, and discuss the notion that non-invasive biofilms are principal lifestyle of S. pneumoniae.